Mobile Broadcast DRM Based on User Identity Card. (11th November 2007) - Lee Lee, Byung-Rae Byung-Rae
Abstract : The current mobile broadcast systems do not provide efficient solution for consumption of service and content based on the user identity card such as a smartcard. This prevents users from consuming broadcast service and contents independent of a specific terminal (e.g., the one used for registration or purchase). To provide usage of broadcast services based on the user identity card, mutual authentication needs to be established among the service provider, the terminal, and the user identity card whenever the terminal is changed. The crucial element for this is assuring the service provider, the terminal, and the user identity card by authenticating each entity to the other entities. In this paper, we propose the new authentication scheme, which provides efficient scheme for three kinds of mutual authentications among the service provider, the terminal, and the user identity card. We also construct mobile broadcast DRM system based on the proposed authentication scheme for consumption of broadcast services with multiple terminals.